Pemanfaatan Silika Abu Boiler Kelapa Sawit sebagai Adsorben dalam Penjernihan Air Sungai - Ari Sukma Langgeng Wijaya; Mahyunis Mahyunis (Lembaga Teewan Journal Solutions, 2026)
This study investigated the effectiveness of silica extracted from palm oil boiler ash as an adsorbent for improving river wastewater quality. A quantitative experimental method with a 2 × 3 factorial design was employed by varying silica adsorbent dosage (3 g and 5 g) and contact time (30, 60, and 90 minutes). River wastewater samples were analyzed before and after adsorption based on turbidity, Total Suspended Solids (TSS), pH, and iron (Fe) concentration. The results demonstrated that silica extracted from palm oil boiler ash effectively improved water quality by reducing TSS, turbidity, and Fe levels. Increasing the adsorbent dosage and extending the contact time significantly enhanced adsorption performance. The optimum treatment was achieved using 5 g of silica with a 90-minute contact time, reducing TSS from 146 to 48 mg/L, turbidity from 21.66 to 11.20 NTU, and Fe concentration from 0.2821 to 0.2221 mg/L, while maintaining pH within acceptable limits. The highest removal efficiency was observed for TSS (67.12%), followed by turbidity (48.29%) and Fe (21.27%). These findings indicate that silica derived from palm oil boiler ash is a promising, environmentally friendly, and cost-effective alternative adsorbent for wastewater treatment.